Campus officers' sanctioning of alcohol-involved crime: influences on discretionary decision-making. (3rd May 2016) - Allen, Andrea
Abstract : Universities are a hotbed of alcohol consumption, which is a major contributor to campus crime. In the US, campus police are responsible for handling crimes on campus. Like municipal police, campus officers are afforded the power to make discretionary sanctioning decisions. The question for this paper is what affects those decisions? To explore that topic, data collected during ride-alongs with campus officers are analyzed. Campus officers explained their sanctions as being affected by nine factors. The findings suggest that influences on campus and municipal officers' sanctioning decisions are largely similar. The paper concludes by discussing implications for future research.